Palaeoboganium gen. nov. from the Middle Jurassic of China (Coleoptera: Cucujoidea: Boganiidae): the first cycad pollinators?. (16th March 2018) - Liu, Zhenhua; Ślipiński, Adam; Lawrence, John F.; Ren, Dong; Pang, Hong
Abstract : Palaeoboganium jurassicum gen. et sp. nov. is described from the Middle Jurassic Daohugou formation in northern China. Palaeoboganium jurassicum is the first fossil representative of the enigmatic family Boganiidae, currently known from Gondwanan localities in South Africa, Australia and New Caledonia. Based on a phylogenetic analysis of adult external characters, Palaeoboganium is recovered as the sister group of Paracucujus Sen Gupta & Crowson and Metacucujus Endrödy-Younga & Crowson (Paracucujinae), whose adults pollinate cycads in Australia and South Africa. Based on phylogenetic evidence this taxon is suggested to be a potential pollinator of Jurassic cycads. http://zoobank.org/urn:lsid:zoobank.org:pub:7EDB8295-5EF3-40ED-9A84-479AD23611AF